1978
DOI: 10.1037/0021-843x.87.4.418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol and cognitive set on sexual arousal to deviant stimuli.

Abstract: Forty-eight undergraduate male social drinkers were randomly assigned to one of two expectancy set conditions in which they were led to believe that the beverage they were administered contained alcohol or no alcohol. For half of the subjects in each expectancy condition, the beverage was an alcoholic malt liquor; the others drank a nonalcoholic malt beverage. After their drinks, changes in penile tumescence in response to normal and deviant tape recordings and to self-generated fantasy were measured physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(67 citation statements)
references
References 19 publications
3
64
0
Order By: Relevance
“…Men who thought they were drinking alcohol were more sexually aroused by depictions of forced and consensual sex than were men who did not think they had consumed alcohol (Briddell et al, 1978;George & Marlatt, 1986;George & Norris, 1991;George, Stoner, Norris, Lopez, & Lehman, 2000). In these studies, it was the belief that one had consumed alcohol, rather than alcohol consumption, which affected men's sexual arousal.…”
Section: Perpetrators' Personality Characteristicsmentioning
confidence: 98%
“…Men who thought they were drinking alcohol were more sexually aroused by depictions of forced and consensual sex than were men who did not think they had consumed alcohol (Briddell et al, 1978;George & Marlatt, 1986;George & Norris, 1991;George, Stoner, Norris, Lopez, & Lehman, 2000). In these studies, it was the belief that one had consumed alcohol, rather than alcohol consumption, which affected men's sexual arousal.…”
Section: Perpetrators' Personality Characteristicsmentioning
confidence: 98%
“…[16][17][18][19][20] In studies where physical exertion is minimized during arousal, such as when men are exposed to visual sexual stimulation while seated in a laboratory, heart rate shows variable and complex patterns. For example, several studies indicate decreasing heart rate during arousal, 21,22 perhaps due in part to increased attentiveness to sexual stimuli. 23,24 Others suggest a biphasic response-initial deceleration followed by acceleration-or a diverging response, with some men showing accelerated heart rate and variable penile tumescence and others showing a more stable heart rate with smooth tumescence.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some studies have suggested that the fact that subject's believe they are drinking an alcoholic beverage, even with no real alcohol administration, can increase subjective sexual arousal [8,24,40]. In our study, participants in both groups believed they had ingested red wine.…”
Section: Discumentioning
confidence: 61%
“…Fast Fourier Transform (FFT) analyses were then applied to the artifact-free data in 2-s epoch samples, with the spectral graph ranging from 0.5 -30 Hz at 0.5 Hz-resolution. FFTs were performed using EEGmagic software [38] to calculate: 1) absolute power (AP), defined as the power density of each frequency band expressed in microvolts squared (μV2/Hz); 2) relative power (RP), the proportional contribution of each band to total power across 1 -30 Hz and; 3) correlation, the degree of functional coupling between the prefrontal and parietal or temporal cortices in each one of the six frequency bands monitored: namely, delta (1 -3.5 Hz), theta (4 -7.75 Hz), alpha1 (8 -10.5 Hz), alpha2 (11 -13.5 Hz), beta1 (14 -19.5 Hz) and beta2 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Correlation values were averaged over all epochs of the same condition for each subject and pair of derivations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation